ABOUT SIMPLE ANTI-DIABETIC REMEDIES BY AVICENNA - M.U. SHAROFOVA (Avicenna Tajik State Medical University, 2019)
Objective: To study the principles of the use of anti-diabetic drugs in the medical system of Avicenna based on the features of the «mizaj» of medicines. Methods: For the analysis the understanding of the Avicenna processes of diabetes genesis, the treatment of diabetes and its prevention, screening of his works was carried out: all the books of the five-volume «Canon of Medicine», medical treatises «Al-Vohiya» («Recipe Code»), «Ash-Shifa» («Book of Healing»), «The Treatise on Medical Care», «The Treatise on Medicines», «The Treatise on Heart Medication», «The Treatise on Pulse». Results: Screening of Avicenna's works allowed allocating 84 medicines used for diabetes therapy and prevention. Most of the remedies have plant origins, including gums and gum-resins. The list also contains mineral and animal remedies. Most anti-diabetic remedies on Avicenna have «hot nature», i.e. warming and leaching properties. Cooling action with «cold nature» products was aimed at reducing the body's fluid loss in diabetes. The combination of Avicenna's various remedies recommended balances their effects on the body and alternating their use will add the correction of the «mizaj» in diabetes. Conclusion: Treatment of diabetes, as a condition of poly-morbidity with numerous metabolic disorders, requires taking into account the relationship between multicomponent phytochemical composition, the versatility of the range of therapeutic actions of natural origin remedies and the features of the «mizaj» of the patient's body